The European Digital Library and authors´ rights - Riera, Patricia (Anuario ThinkEPI, 2008)
The development of the European Digital Library, a project that will give European citizens access to our cultural heritage, raises many questions about this project´s compatibility with copyright protection for authors, which has been under discussion by the European Union in recent years.
Keywords: Copyright; Intellectual property; Regulation; Legislation; European Union; Digital libraries; Information access.